Preparation method of high-purity positive photoresist based on quaternary copolymer resin
Patent Information
- Application Number
- CN202611153129.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-30
AI Technical Summary
SU-8虽具有较高的分辨率和耐化学性,但SU-8与硅/金属基底之间主要依赖物理吸附和机械咬合,缺乏牢固的化学键连接,在流体冲刷和热循环的长期作用下极易发生开裂或剥离
[0014]本发明光刻胶中,甲基丙烯酸叔丁酯提供酸敏脱保护位点,β-羟基-γ-丁内酯甲基丙烯酸酯改善碱显影浸润性,二者协同能够使光刻胶具备高对比度与高分辨率,配合碱性添加剂对酸扩散的精确控制,可实现亚微米级微流体通道的精准成型,分辨率可达0.5μm以下,满足高密度微流体散热结构的制造需求。本发明光刻胶通过引入含金刚烷基的甲基丙烯酸酯,其大体积刚性金刚烷结构将树脂的玻璃化转变温度提升至150°C以上,赋予光刻胶优异的抗化学腐蚀性和热稳定性,显影后的未曝光区域经高温后固化处理,可从光刻胶转变为永久结构材料。本发明光刻胶中,β-羟基-γ-丁内酯甲基丙烯酸酯的β-羟基与四氢糠基甲基丙烯酸酯(THFMA)的四氢呋喃环结构产生协同效应,增强了树脂与硅/金属基底之间的界面结合力,从而有效防止微流体通道在长期使用中发生分层或泄漏。本发明光刻胶通过“离子交换-螯合吸附-纳滤膜分离-重沉淀”多级联用纯化工艺,将树脂中金属离子的总含量降至≤2ppb,单项金属离子≤0.5ppb,满足半导体级光刻胶的纯度要求,从根本上消除了金属离子对芯片性能和良率的影响。
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing a high-purity positive photoresist based on a quaternary copolymer resin. Background Technology
[0002] With the explosive growth in computing power demands from artificial intelligence, the power density of high-performance chips has exceeded kilowatts per square centimeter. Traditional air cooling and indirect liquid cooling solutions are insufficient to meet the heat dissipation requirements of high-performance chips due to low heat dissipation efficiency, large system size, poor reliability, and the risk of leakage. Embedded microfluidic heat dissipation technology, by directly constructing microscale fluid channels inside the chip or in the packaging substrate, achieves chip-level direct heat dissipation without the need for an external liquid cooling system, and is considered one of the key technological paths to overcome the heat dissipation bottleneck. In this refined manufacturing process, photoresist, as the core functional material for achieving precise transfer of microfluidic channel patterns and selective protection of regions, directly determines the accuracy of the channel structure, interface quality, and the heat dissipation effect of the final heat dissipation device.
[0003] Currently, photoresists used to construct embedded microfluidic channels with widths of 5-10 micrometers mainly include negative photoresists, represented by SU-8, and positive photoresists, represented by AZ 4620. While SU-8 offers high resolution and chemical resistance, its adhesion to silicon / metal substrates relies primarily on physical adsorption and mechanical bonding, lacking strong chemical bonds. This makes it highly susceptible to cracking or peeling under long-term fluid erosion and thermal cycling. AZ 4620, a traditional phenolic resin-diazonaphthoquinone system positive photoresist, is only used as a temporary mask and cannot be converted into a permanent structural material through high-temperature post-curing. It requires additional bonding processes to achieve channel sealing, and its low glass transition temperature makes it prone to softening and deformation during subsequent high-temperature packaging or long-term service. Therefore, both types of photoresists share the common problem of insufficient adhesion to the substrate interface in practical applications, leading to delamination or leakage of microfluidic channels after only tens of hours of service, severely limiting the reliability and lifespan of embedded microfluidic heat dissipation technology. Summary of the Invention
[0004] Purpose of the invention: The purpose of this invention is to provide a method for preparing a high-purity positive photoresist based on a quaternary copolymer resin. The photoresist prepared by this method has excellent interfacial adhesion to silicon / metal substrates, so that the constructed microfluidic channels do not undergo channel delamination or leakage under long-term effects of fluid flushing and thermal cycling (after 72 hours of use). At the same time, it also has high resolution, high contrast, high glass transition temperature (Tg>150℃) and excellent chemical corrosion resistance.
[0005] Technical solution: The preparation method of high-purity positive photoresist based on quaternary copolymer resin according to the present invention includes the following steps:
[0006] (1) Synthesis of quaternary copolymer resin: tert-butyl methacrylate, adamantyl methacrylate, β-hydroxy-γ-butyrolactone methacrylate, tetrahydrofurfuryl methacrylate, free radical initiator and chain transfer agent are dissolved in a solvent and subjected to free radical copolymerization under inert gas protection. After the reaction, a quaternary copolymer resin solution is obtained; wherein, the mass ratio of tert-butyl methacrylate, adamantyl methacrylate, β-hydroxy-γ-butyrolactone methacrylate and tetrahydrofurfuryl methacrylate is 50~60:25~35:10:5;
[0007] (2) The quaternary copolymer resin solution was purified in multiple stages by passing it through an ion exchange resin column, a chelation resin column and a nanofiltration membrane module, and then subjected to reprecipitation to obtain a high-purity resin solution with a total metal ion content ≤2ppb.
[0008] (3) Photoresist preparation: Add photoacid generator, alkaline additive and solvent to the resin solution, stir and filter to obtain positive photoresist.
[0009] In step (1), the free radical initiator is azobisisobutyronitrile (AIBN), and its addition amount is 1.5-2% of the total mass of the polymer monomers. The chain transfer agent is dodecyl mercaptan (CAS No. 112-55-0), and its addition amount is 1.5-2% of the total mass of the polymer monomers. The adamantyl methyl methacrylate is at least one of 2-methacryloyloxyadamantane (AdMA), 2-ethyl-2-methacryloyloxyadamantane (EtAdMA), or 2-isopropyl-2-methacryloyloxyadamantane (IPAMA). The solvent is propylene glycol methyl ether (PGME) or propylene glycol methyl ether acetate (PGMEA). During the reaction, there are at least two replenishment processes, with each replenishment of free radical initiator amounting to 0.1-0.15% of the total mass of the polymer monomers. The purpose of replenishment is to replenish the consumed initiator as the polymerization reaction proceeds, maintain the free radical concentration in the system, ensure the full conversion of residual monomers, and improve the total monomer conversion rate (≥95%). At the same time, it avoids the violent exothermic reaction and widening of molecular weight distribution caused by adding excessive initiator at one time.
[0010] In step (1), the reaction temperature is 75~85℃ and the reaction time is 5~8h.
[0011] In step (1), the solid content of the obtained quaternary copolymer resin solution is 30 wt.%. The purpose of adding PGME to adjust the solid content of the quaternary copolymer resin solution to 30 wt.% is that after the polymerization reaction, the solid content of the reaction system is usually high (about 40~50 wt.%), and the viscosity is high, which is not conducive to subsequent ion exchange and filtration operations. Diluting to 30% can reduce the viscosity of the solution and improve the mass transfer efficiency and operational fluidity during the purification process. The number average molecular weight (Mn) of the obtained quaternary copolymer resin is about 12000, and the molecular weight distribution (PDI) is 1.8.
[0012] In step (2), the ion exchange resin column includes a cation exchange resin column, an anion exchange resin column, and a mixed ion exchange resin column; the chelating resin column is filled with iminodiacetic acid type chelating resin; the nanofiltration membrane assembly is a hydrophilic polyamide composite membrane with a molecular weight cutoff of 500~800 Da and an operating pressure of 10~20 bar; the reprecipitation treatment involves dropping the nanofiltration treated resin solution into 10~20 times the volume of ultrapure water for precipitation, repeating 2~3 times.
[0013] In step (3), the photoacid generator is a compound that can produce strong acids (such as sulfonic acids) under deep ultraviolet light (such as 248nm KrF) or i-line (365nm) irradiation, such as triphenylthionium salt (TPS), diphenyliodonium salt (DPI), or naphthalimide sulfonate (nonionic PAG); it is a chemical switch that triggers the deprotection reaction of tert-butyl methacrylate and achieves positive patterning; its addition amount is 6-8% of the mass of the quaternary copolymer resin. The alkaline additive is tetrabutylammonium hydroxide (TBAH), tetramethylammonium hydroxide (TMAH), or triethylamine (TEA), which quenches excess acid diffused into the unexposed area, inhibits acid diffusion, thereby improving resolution and reducing line edge roughness (LER); its addition amount is 5-15% of the mass of the photoacid generator, preferably 10%. The solvent is at least one of propylene glycol methyl ether (PGME), propylene glycol methyl ether acetate (PGMEA), or ethyl lactate. Its function is to dissolve the components and provide a suitable processing viscosity, so that the solid content of the final positive photoresist is 5~15 wt.%, preferably 10 wt.%.
[0014] In the photoresist of this invention, tert-butyl methacrylate provides acid-sensitive deprotection sites, and β-hydroxy-γ-butyrolactone methacrylate improves alkaline development wettability. The synergistic effect of these two components enables the photoresist to possess high contrast and high resolution. Combined with alkaline additives for precise control of acid diffusion, it allows for the precise molding of submicron-level microfluidic channels with a resolution below 0.5 μm, meeting the manufacturing requirements of high-density microfluidic heat dissipation structures. By introducing adamantyl methyl methacrylate, the large-volume rigid adamantane structure of this photoresist raises the glass transition temperature of the resin to above 150°C, endowing the photoresist with excellent chemical corrosion resistance and thermal stability. The unexposed areas after development can be transformed into permanent structural materials through high-temperature post-curing. In the photoresist of this invention, the β-hydroxyl group of β-hydroxy-γ-butyrolactone methacrylate and the tetrahydrofuran ring structure of tetrahydrofurfuryl methacrylate (THFMA) produce a synergistic effect, enhancing the interfacial bonding between the resin and the silicon / metal substrate, thereby effectively preventing delamination or leakage of the microfluidic channels during long-term use. The photoresist of this invention uses a multi-stage purification process of "ion exchange-chelation adsorption-nanofiltration membrane separation-reprecipitation" to reduce the total content of metal ions in the resin to ≤2ppb and the content of individual metal ions to ≤0.5ppb, which meets the purity requirements of semiconductor-grade photoresist and fundamentally eliminates the impact of metal ions on chip performance and yield.
[0015] Beneficial Effects: Compared with the prior art, the present invention has the following significant advantages: The positive photoresist prepared by the present invention can be used to construct embedded microfluidic channels with a channel width of less than 5 micrometers. The photoresist of the present invention has high resolution and high contrast, so it can obtain steep sidewall profiles and uniform linewidth during deep ultraviolet exposure in the process of constructing embedded microfluidic channels. Secondly, the photoresist of the present invention has a high glass transition temperature (Tg>150℃) and excellent chemical corrosion resistance. The photoresist can form a permanent structure after high-temperature curing after development. Moreover, due to its good interfacial adhesion with the substrate, it can withstand long-term erosion by coolant and thermal shock of subsequent packaging processes without delamination. Finally, the total metal ion content in the photoresist of the present invention is ≤2ppb, which can effectively avoid the impact of metal ion impurities on chip performance and yield. Detailed Implementation
[0016] Example 1
[0017] This invention relates to a method for preparing high-purity positive photoresist based on quaternary copolymer resin, comprising the following steps:
[0018] (1) In a four-necked flask equipped with a stirrer, thermometer, nitrogen delivery tube and condenser, add propylene glycol methyl ether (PGME, 233g) as the base material, start stirring and heat to 80℃ and keep warm; add tert-butyl methacrylate (CAS No. 585-07-9) (TBMA, 55g), 2-isopropyl-2-methacryloyloxyadamantane (IPAMA, 30g), β-hydroxy-γ-butyrolactone methacrylate (CAS No. 13) Mix 10g of 0224-95-2 (tetrahydrofurfuryl methacrylate, 5g), 1.5g of azobisisobutyronitrile (AIBN), and 1.5g of dodecyl mercaptan (chain transfer agent) to prepare a monomer mixture. Under nitrogen protection, the monomer mixture is added dropwise to a four-necked flask at 80°C over 3 hours at a uniform rate. After the addition is complete, the first AIBN solution (composed of 0.1g AIBN + 15g PGME) is added, and the mixture is kept warm for 1 hour. The second AIBN solution (composed of 0.1g AIBN + 15g PGME) is added, and the mixture is kept warm for 1 hour to consume the remaining monomer. After the warming is complete, heating is stopped, the mixture is cooled to room temperature, and PGME is added to adjust the solid content to 30wt.%. The mixture is then discharged and filtered to obtain a quaternary copolymer resin solution (denoted as R1).
[0019] According to gel permeation chromatography (GPC), the number average molecular weight (Mn) of the quaternary copolymer resin in sample R1 was approximately 12,000, and the molecular weight distribution (PDI) was 1.8.
[0020] (2) The quaternary copolymer resin solution from step (1) was sequentially passed through a strong acid cation exchange resin column (Amberlyst® 15, Rohm and Haas), a strong base anion exchange resin column (Amberlyst® A26, Rohm and Haas), and a mixed ion exchange resin column (Amberlyst® 15 and Amberlyst® A26 mixed at a volume ratio of 1:1) at a flow rate of 1.0 BV / h; then the effluent from the ion exchange resin column was passed through a chelating resin column (Chelex® 100, Bio-Rad, Na...) at a flow rate of 2.0 BV / h. +The resin solution was first chelated with an iminodiacetic acid chelating resin. The chelated resin solution was then passed through a dual-stage tandem nanofiltration membrane module (DK-8040F, Suez Corporation, hydrophilic polyamide composite membrane). Finally, the nanofiltration-treated resin solution was dropped into 15 times its volume (15 times the volume of the resin solution) of ultrapure water (resistivity ≥18.2 MΩ·cm) to precipitate. After centrifugation, it was redissolved in electronic-grade PGMEA (electronic-grade propylene glycol methyl ether acetate), and the precipitation-dissolution process was repeated twice. Inductively coupled plasma mass spectrometry (ICP-MS) analysis showed that the total metal ion content in the resin solution before purification (solid content 30 wt.%) was 1895 ppb, of which Na... + 850ppb, K + 420ppb, Ca 2+ 310ppb, Fe 3+ 180ppb, Cu 2+ :65ppb、Ni 2+ 42ppb, Cr 3+ The total metal ion content in the purified resin solution (solid content of 30 wt.%) was 1.7 ppb, and the content of each individual metal ion was ≤0.5 ppb.
[0021] (3) Take 333.3g of the purified quaternary copolymer resin solution from step (2) (the resin solution contains 100g of resin solids), add the photoacid-generating agent triphenylthionium trifluoromethanesulfonate (CAS66003-78-9) (6.0g, accounting for 6% of the resin solid mass), the alkaline additive tetrabutylammonium hydroxide (TBAH, 0.6g, accounting for 10% of the photoacid-generating agent mass), and propylene glycol methyl ether acetate (PGMEA, about 620g) to it, and adjust the total volume of the solution to 1L; stir the resulting mixture mechanically at 600rpm for 2 hours, and then filter it through a 0.2μm PTFE filter to obtain a uniform and stable positive photoresist (denoted as A1); the solid content of positive photoresist A1 is about 10wt.%.
[0022] The microfluidic heat dissipation structure was constructed based on the positive photoresist prepared in Example 1, and the specific steps are as follows:
[0023] Step 1: Use a spin coater to coat photoresist A1 onto a silicon-based adapter board (the surface of which has been treated with HMDS primer). The spin coating parameters are: 500 rpm / 5s for the first stage and 2000 rpm / 30s for the second stage. Then, preheat the film on a hot plate at 110°C for 90 seconds to obtain a photoresist film with a thickness of about 8~9μm.
[0024] Step 2: Exposure is performed using a 248nm KrF lithography machine with a mask having a linewidth / pitch of 5μm and an exposure dose of 35mJ / cm². 2After exposure, the substrate was baked on a hot plate at 120°C (PEB, 90 seconds). The exposed substrate (with photoresist layer) was then immersed in a 2.38 wt.% TMAH aqueous solution for development for 60 seconds. After development, it was rinsed with deionized water and dried with nitrogen. Next, it was wet etched at 60°C using a saturated hydrochloric acid-ferric chloride solution for 35 minutes. After etching, it was rinsed with deionized water and dried with nitrogen. The developed pattern on the substrate was clear, the edges of the microfluidic channels were steep, the measured linewidth was 4.8 μm, and the resolution reached the submicron level.
[0025] Step 3: After development, the photoresist layer is subjected to high-temperature post-curing treatment on a hot plate at 180°C for 2 hours to transform the resin in the unexposed area into a permanent structural material. A glass cover plate is then bonded above the cured microfluidic channel to complete the fabrication of the embedded microfluidic heat dissipation structure.
[0026] The glass transition temperature (Tg) of the cured photoresist was tested using a dynamic thermomechanical analyzer (DMA) and the result was 162℃.
[0027] Using a heat flux density testing platform, at an input power density of 500 W / cm² 2 Under high heat load conditions, the embedded microfluidic heat dissipation structure prepared in Example 1 operated stably for 72 hours without channel delamination (delamination refers to the peeling between the photoresist and the silicon substrate) or leakage, and the thermal resistance was 0.15 K·cm. 2 / W.
[0028] After being continuously rinsed with deionized water at a flow rate of 10 mL / min for 168 hours, the channel sidewalls remained intact with no corrosion marks; the adhesion test (adhesion between photoresist and silicon substrate) (cross-cut test) achieved a grade of 0.
[0029] Example 2
[0030] The preparation method of the photoresist in Example 2 is basically the same as that in Example 1, except that: in step (1), the amount of monomers added to the quaternary copolymer resin is adjusted: tert-butyl methacrylate (tBMA) is 50g, 2-methacryloyloxyadamantane (AdMA) is 35g, β-hydroxy-γ-butyrolactone methacrylate is 10g, and tetrahydrofurfuryl methacrylate (THFMA) is 5g; the resin is synthesized according to the same method to obtain quaternary copolymer resin solution R2. The number average molecular weight (Mn) of the quaternary copolymer resin in R2 is about 11800 and the molecular weight distribution (PDI) is 1.8, as determined by gel permeation chromatography (GPC); the solid content of the quaternary copolymer resin solution R2 is 30wt.%. The purification of the resin solution in step (2) and the preparation of the photoresist in step (3) are exactly the same as in Example 1, to obtain positive photoresist A2, the solid content of which is about 10wt.%.
[0031] The microfluidic heat dissipation structure was constructed based on the positive photoresist prepared in Example 2, and the specific steps are as follows:
[0032] Step 1: Use a spin coater to coat photoresist A1 onto a silicon-based adapter board (the surface of which has been treated with HMDS primer). The spin coating parameters are: 500 rpm / 5s for the first stage and 2000 rpm / 30s for the second stage. Then, preheat the film on a hot plate at 110°C for 90 seconds to obtain a photoresist film with a thickness of about 8~9μm.
[0033] Step 2: Exposure is performed using a 248nm KrF lithography machine with a mask having a linewidth / pitch of 5μm and an exposure dose of 40mJ / cm². 2 After exposure, the substrate was baked on a hot plate at 120°C (PEB, 90 seconds). The exposed substrate (with photoresist layer) was then immersed in a 2.38 wt.% TMAH aqueous solution for development for 55 seconds. After development, it was rinsed with deionized water and dried with nitrogen. Next, it was wet etched at 60°C using a saturated hydrochloric acid-ferric chloride solution for 35 minutes. After etching, it was rinsed with deionized water and dried with nitrogen. The developed pattern on the substrate was clear, and the edges of the microfluidic channels were steep, resulting in a clear microchannel pattern with a linewidth of 4.5 μm.
[0034] Step 3: After development, the photoresist layer is subjected to high-temperature post-curing treatment on a hot plate at 180°C for 2 hours to transform the resin in the unexposed area into a permanent structural material. A glass cover plate is then bonded above the cured microfluidic channel to complete the fabrication of the embedded microfluidic heat dissipation structure.
[0035] The glass transition temperature (Tg) of the cured photoresist was measured using a dynamic thermomechanical analyzer (DMA), and the result was 165℃. A heat flux density test platform was used with an input power density of 520 W / cm². 2 Under high heat load conditions, the embedded microfluidic heat dissipation structure prepared in Example 2 operated stably for 72 hours without channel delamination or leakage. After continuous rinsing with deionized water at a flow rate of 10 mL / min for 72 hours, the channel sidewalls remained intact without any corrosion marks.
[0036] Example 3
[0037] The preparation method of the photoresist in Example 3 is basically the same as that in Example 1, except that the amount of monomers added to the quaternary copolymer resin in step (1) is adjusted as follows: tert-butyl methacrylate (tBMA) is 60g, 2-isopropyl-2-methacryloyloxyadamantane is 25g, β-hydroxy-γ-butyrolactone methacrylate is 10g, and tetrahydrofurfuryl methacrylate (THFMA) is 5g. The resin is synthesized according to the same method to obtain the quaternary copolymer resin solution R3. The number average molecular weight (Mn) of the quaternary copolymer resin in R3 is about 12200 and the molecular weight distribution (PDI) is 1.8, as determined by gel permeation chromatography (GPC). The solid content of the quaternary copolymer resin solution R3 is 30wt.%.
[0038] The purification of the resin solution in step (2) is exactly the same as in Example 1;
[0039] In step (3) during the photoresist preparation process, in Example 3, the amount of photoacid generator triphenylthionium trifluoromethanesulfonate added was 8% (8.0g) of the solid mass of the resin, and the amount of alkaline additive added was 15% (1.2g) of the photoacid generator, resulting in positive photoresist A3; the solid content of positive photoresist A3 was approximately 10wt.%.
[0040] The microfluidic heat dissipation structure was constructed based on the positive photoresist prepared in Example 3, and the specific steps are as follows:
[0041] Step 1: Use a spin coater to coat photoresist A1 onto a silicon-based adapter board (the surface of which has been treated with HMDS primer). The spin coating parameters are: 500 rpm / 5s for the first stage and 2000 rpm / 30s for the second stage. Then, preheat the film on a hot plate at 110°C for 90 seconds to obtain a photoresist film with a thickness of about 8~9μm.
[0042] Step 2: Exposure is performed using a 248nm KrF lithography machine with a mask having a linewidth / pitch of 5μm and an exposure dose of 40mJ / cm². 2 After exposure, the substrate was baked on a hot plate at 120°C (PEB, 90 seconds). The exposed substrate (with photoresist layer) was then immersed in a 2.38 wt.% TMAH aqueous solution for development for 55 seconds. After development, it was rinsed with deionized water and dried with nitrogen. Next, it was wet etched at 60°C using a saturated hydrochloric acid-ferric chloride solution for 35 minutes. After etching, it was rinsed with deionized water and dried with nitrogen. The developed pattern on the substrate was clear, and the edges of the microfluidic channels were steep, resulting in a clear microchannel pattern with a linewidth of 4.5 μm.
[0043] Step 3: After development, the photoresist layer is subjected to high-temperature post-curing treatment on a hot plate at 180°C for 2 hours to transform the resin in the unexposed area into a permanent structural material. A glass cover plate is then bonded above the cured microfluidic channel to complete the fabrication of the embedded microfluidic heat dissipation structure.
[0044] The glass transition temperature (Tg) of the cured photoresist was measured using a dynamic thermomechanical analyzer (DMA), and the result was 165℃. A heat flux density test platform was used with an input power density of 520 W / cm². 2 Under high heat load conditions, the embedded microfluidic heat dissipation structure prepared in Example 3 operated stably for 72 hours without channel delamination or leakage. After continuous rinsing with deionized water at a flow rate of 10 mL / min for 72 hours, the channel sidewalls remained intact without any corrosion marks.
[0045] Comparative Example 1
[0046] The preparation method of the photoresist in Comparative Example 1 is basically the same as that in Example 1, except that: in step (1), 2-isopropyl-2-methacryloyloxyadamantane is not added during the preparation of the copolymer resin. Specifically, 70g of tert-butyl methacrylate (tBMA), 20g of β-hydroxy-γ-butyrolactone methacrylate, and 10g of tetrahydrofurfuryl methacrylate (THFMA) are used. The resin is synthesized in the same way to obtain a copolymer resin solution. The number average molecular weight (Mn) of the copolymer resin is about 11800 and the molecular weight distribution (PDI) is 1.8 as determined by gel permeation chromatography (GPC). The solid content of the copolymer resin solution is 30wt.%. The purification of the resin solution in step (2) and the preparation of the photoresist in step (3) are exactly the same as in Example 1 to obtain a positive photoresist with a solid content of about 10wt.%.
[0047] The positive photoresist obtained in Comparative Example 1 was used to prepare a microfluidic heat dissipation structure using the same method as in Example 1.
[0048] Performance testing showed that a microchannel pattern with a linewidth of 6.5 μm was finally obtained, with slight tilting of the pattern sidewalls. The glass transition temperature (Tg) of the cured photoresist was measured using a dynamic thermomechanical analyzer (DMA), and the result was 118 °C. A heat flux density test platform was used at an input power density of 250 W / cm². 2 Under high heat load conditions, the embedded microfluidic heat dissipation structure prepared in Comparative Example 1 exhibited channel deformation after 36 hours of operation, failing to meet the high-power heat dissipation requirements. After continuous rinsing with deionized water at a flow rate of 10 mL / min for 72 hours, obvious delamination and leakage appeared at the channel edges.
[0049] Comparative Example 2
[0050] The preparation method of the photoresist in Comparative Example 2 is basically the same as that in Example 1, except that in step (1), tetrahydrofurfuryl methacrylate is not added during the preparation of the copolymer resin. Specifically, 60g of tert-butyl methacrylate, 30g of 2-isopropyl-2-methacryloyloxyadamantane, and 10g of β-hydroxy-γ-butyrolactone methacrylate are used. The resin is synthesized in the same way to obtain a copolymer resin solution. The number average molecular weight (Mn) of the copolymer resin is about 12,000 and the molecular weight distribution (PDI) is 1.8 as determined by gel permeation chromatography (GPC). The solid content of the copolymer resin solution is 30 wt.%. The purification of the resin solution in step (2) and the preparation of the photoresist in step (3) are exactly the same as in Example 1 to obtain a positive photoresist with a solid content of about 10 wt.%.
[0051] The positive photoresist obtained in Comparative Example 2 was used to prepare a microfluidic heat dissipation structure using the same method as in Example 1.
[0052] Performance testing showed that a microchannel pattern with a linewidth of 5.5 μm was finally obtained. The glass transition temperature (Tg) of the cured photoresist was measured using a dynamic thermomechanical analyzer (DMA), and the result was 160℃. A heat flux density test platform was used at an input power density of 500 W / cm². 2 Under high heat load conditions, the embedded microfluidic heat dissipation structure prepared in Comparative Example 2 exhibited channel deformation after 60 hours of operation. After continuous rinsing with deionized water at a flow rate of 10 mL / min for 72 hours, significant delamination occurred at the channel edges, and leakage occurred in some areas. The adhesion test (adhesion between photoresist and silicon substrate) (cross-cut test) yielded a grade of 2.
[0053] Comparative Example 3
[0054] The preparation method of the photoresist in Comparative Example 3 is basically the same as that in Example 1, except that in step (1), β-hydroxy-γ-butyrolactone methacrylate is not added during the preparation of the copolymer resin. Specifically, 65g of tert-butyl methacrylate, 30g of 2-isopropyl-2-methacryloyloxyadamantane, and 5g of tetrahydrofurfuryl methacrylate are used. The resin is synthesized in the same way to obtain a copolymer resin solution. The number average molecular weight (Mn) of the copolymer resin is about 11800 and the molecular weight distribution (PDI) is 1.8 as determined by gel permeation chromatography (GPC). The solid content of the copolymer resin solution is 30wt.%. The purification of the resin solution in step (2) and the preparation of the photoresist in step (3) are exactly the same as in Example 1, and a positive photoresist is obtained with a solid content of about 10wt.%.
[0055] The positive photoresist obtained in Comparative Example 3 was used to prepare a microfluidic heat dissipation structure using the same method as in Example 1.
[0056] Performance testing showed that the resolution of the microchannel pattern obtained after development was 8.0 μm, and obvious roughness and scum appeared on the sidewalls of the pattern after development. The exposure dose needed to be increased to 60 mJ / cm. 2 Only then can it be fully developed.
[0057] Comparative Example 4
[0058] The preparation method of the photoresist in Comparative Example 4 is basically the same as that in Example 1, except that: in step (1), no chain transfer agent dodecyl mercaptan is added during the preparation of the quaternary copolymer resin, and the final quaternary copolymer resin solution is obtained. According to gel permeation chromatography (GPC), the number average molecular weight (Mn) of the quaternary copolymer resin is about 45,000 and the molecular weight distribution (PDI) is 2.8; the solid content of the quaternary copolymer resin solution is 30 wt.%; the purification of the resin solution in step (2) and the preparation of the photoresist in step (3) are exactly the same as in Example 1, and a positive photoresist is obtained with a solid content of about 10 wt.%.
[0059] The positive photoresist obtained in Comparative Example 4 was used to prepare a microfluidic heat dissipation structure using the same method as in Example 1.
[0060] Performance tests showed that the high molecular weight and wide molecular weight distribution of the resin led to a significant increase in the viscosity of the photoresist solution, resulting in poor uniformity of the spin-coated film. The resolution of the microchannel pattern obtained after development was only 13.6 μm, and the roughness of the line edges was significantly increased, failing to meet the precision requirements of microfluidic channels. After continuous rinsing with deionized water at a flow rate of 10 mL / min for 72 hours, severe uneven swelling and collapse occurred on the sidewalls of the channels.
[0061] Comparative Example 5
[0062] The preparation method of the photoresist in Comparative Example 5 is basically the same as that in Example 1, except that in step (1), 3g of chain transfer agent dodecyl mercaptan is added during the preparation of the quaternary copolymer resin to finally obtain a quaternary copolymer resin solution. The number average molecular weight (Mn) of the quaternary copolymer resin is about 6500 and the molecular weight distribution (PDI) is 1.7, as determined by gel permeation chromatography (GPC); the solid content of the quaternary copolymer resin solution is 30wt.%; the purification of the resin solution in step (2) and the preparation of the photoresist in step (3) are exactly the same as in Example 1, and a positive photoresist is obtained with a solid content of about 10wt.%.
[0063] The positive photoresist obtained in Comparative Example 5 was used to prepare a microfluidic heat dissipation structure using the same method as in Example 1.
[0064] Performance testing showed that the microchannel pattern obtained after development had a resolution of 6.2 μm, with slight roughness on the sidewalls. The glass transition temperature (Tg) of the cured photoresist was measured using a dynamic thermomechanical analyzer (DMA), and the result was 145℃. Heat flux density testing showed a result of 420 W / cm². 2 Under the given conditions, the embedded microfluidic heat dissipation structure prepared in Comparative Example 5 underwent channel deformation after 48 hours of operation. This was because the excessive amount of chain transfer agent resulted in a low molecular weight of resin and short polymer chains. The rigidity provided by the adamantyl group was insufficient to maintain a high glass transition temperature, thereby reducing the thermal stability and chemical corrosion resistance of the resin.
[0065] Comparative Example 6
[0066] The preparation method of the photoresist in Comparative Example 6 is basically the same as that in Example 1, except that in step (1), the mass ratio of tert-butyl methacrylate, adamantyl methacrylate, β-hydroxy-γ-butyrolactone methacrylate, and tetrahydrofurfuryl methacrylate in the preparation of the quaternary copolymer resin is 55:25:15:5, specifically: 55g of tert-butyl methacrylate, 25g of 2-isopropyl-2-methacryloyloxyadamantane, and 25g of β-hydroxy-γ-butyrolactone methacrylate. The amount of resin was 15g, and the amount of tetrahydrofurfuryl methacrylate was 5g. The resin was synthesized in the same way to obtain a quaternary copolymer resin solution. The number average molecular weight (Mn) of the quaternary copolymer resin was approximately 12,100 and the molecular weight distribution (PDI) was 1.8, as determined by gel permeation chromatography (GPC). The solid content of the copolymer resin solution was 30 wt.%. The purification of the resin solution in step (2) and the preparation of the photoresist in step (3) were exactly the same as in Example 1 to obtain a positive photoresist with a solid content of approximately 10 wt.%.
[0067] The positive photoresist obtained in Comparative Example 6 was used to prepare a microfluidic heat dissipation structure using the same method as in Example 1.
[0068] Performance testing showed that the microchannel pattern obtained after development had a resolution of 5.6 μm. The glass transition temperature (Tg) of the cured photoresist was measured using a dynamic thermomechanical analyzer (DMA), and the result was 153 °C. Heat flux density testing showed a value of 470 W / cm². 2 Under the same conditions, the embedded microfluidic heat dissipation structure prepared in Comparative Example 6 showed channel deformation after 60 hours of operation. After being continuously flushed with deionized water at a flow rate of 10 mL / min for 168 hours, the sidewalls of the channels swelled and thickened.
[0069] Comparative Example 7
[0070] The preparation method of the photoresist in Comparative Example 7 is basically the same as that in Example 1, except that in step (1), all the initiators are added at once, specifically:
[0071] (1) In a four-necked flask equipped with a stirrer, thermometer, nitrogen delivery tube and condenser, add propylene glycol methyl ether (233g) as the base material, start stirring and heat to 80℃ and keep warm; mix tert-butyl methacrylate (55g), 2-isopropyl-2-methacryloyloxyadamantane (30g), β-hydroxy-γ-butyrolactone methacrylate (10g), tetrahydrofurfuryl methacrylate (5g), azobisisobutyronitrile (1.7g) and dodecyl mercaptan (1.5g) evenly to prepare a monomer mixture; under nitrogen protection, add the monomer mixture dropwise to the four-necked flask at a uniform rate at 80℃ for 3 hours; after the dropwise addition is completed, add the first AIBN solution (AIBN solution is 15g). The PGME composition was added, and the solution was kept warm for 1 hour. Then, a second AIBN solution (composed of 15g PGME) was added, and the solution was kept warm for 1 hour. After the warming was completed, the heating was stopped, the solution was cooled to room temperature, and PGME was added to adjust the solid content to 30wt.%. The solution was discharged and filtered to obtain a quaternary copolymer resin solution. The number average molecular weight (Mn) of the quaternary copolymer resin was determined by gel permeation chromatography (GPC) to be approximately 13500, the molecular weight distribution (PDI) was 2.6, and the solid content of the quaternary copolymer resin solution was 30wt.%. The purification of the resin solution in step (2) and the preparation of the photoresist in step (3) were exactly the same as in Example 1, and a positive photoresist was obtained with a solid content of approximately 10wt.%.
[0072] The positive photoresist obtained in Comparative Example 7 was used to prepare a microfluidic heat dissipation structure using the same method as in Example 1.
[0073] Performance testing showed that the microchannel pattern obtained after development had a resolution of 12.9 μm, with noticeable roughness on the sidewalls and significantly increased line edge roughness. This was because the simultaneous addition of all the initiator resulted in an excessively high free radical concentration in the early stages of the polymerization reaction, leading to a rapid reaction rate and generating a large amount of heat. Local overheating of the system caused a significant broadening of the molecular weight distribution (PDI=2.6), with low-molecular-weight components and high-molecular-weight tails coexisting. This broad molecular weight distribution resulted in inconsistent photoresist development rates; the rapid dissolution of low-molecular-weight components caused rough edges, while the slow dissolution of high-molecular-weight components resulted in development residue, ultimately leading to a decrease in resolution and pattern quality. After continuous rinsing with deionized water at a flow rate of 10 mL / min for 72 hours, uneven corrosion appeared at the channel edges.
Claims
1. A method for preparing a high-purity positive photoresist based on a quaternary copolymer resin, characterized in that, Includes the following steps: (1) Synthesis of quaternary copolymer resin: tert-butyl methacrylate, adamantyl methacrylate, β-hydroxy-γ-butyrolactone methacrylate, tetrahydrofurfuryl methacrylate, free radical initiator and chain transfer agent are dissolved in a solvent and subjected to free radical copolymerization under inert gas protection. After the reaction, a quaternary copolymer resin solution is obtained; wherein, the mass ratio of tert-butyl methacrylate, adamantyl methacrylate, β-hydroxy-γ-butyrolactone methacrylate and tetrahydrofurfuryl methacrylate is 50~60:25~35:10:5; (2) The quaternary copolymer resin solution was purified in multiple stages by passing it through an ion exchange resin column, a chelation resin column and a nanofiltration membrane module, and then subjected to reprecipitation to obtain a high-purity resin solution with a total metal ion content ≤2ppb. (3) Photoresist preparation: Add photoacid generator, alkaline additive and solvent to the resin solution, stir and filter to obtain positive photoresist.
2. The method for preparing high-purity positive photoresist based on quaternary copolymer resin according to claim 1, characterized in that: In step (1), the free radical initiator is azobisisobutyronitrile, and its addition amount is 1.5~2% of the total mass of the polymer monomers; the chain transfer agent is dodecyl mercaptan, and its addition amount is 1.5~2% of the total mass of the polymer monomers.
3. The method for preparing high-purity positive photoresist based on quaternary copolymer resin according to claim 1, characterized in that: In step (1), the adamantyl alkyl-containing methacrylate is at least one of 2-methacryloyloxyadamantane, 2-ethyl-2-methacryloyloxyadamantane or 2-isopropyl-2-methacryloyloxyadamantane.
4. The method for preparing high-purity positive photoresist based on quaternary copolymer resin according to claim 1, characterized in that: In step (1), the solvent is propylene glycol methyl ether or propylene glycol methyl ether acetate.
5. The method for preparing high-purity positive photoresist based on quaternary copolymer resin according to claim 1, characterized in that: In step (1), there are at least two replenishment processes during the reaction, and the amount of free radical initiator added each time is 0.1~0.15% of the total mass of the polymer monomer.
6. The method for preparing high-purity positive photoresist based on quaternary copolymer resin according to claim 1, characterized in that: In step (1), the reaction temperature is 75~85℃ and the reaction time is 5~8h.
7. The method for preparing high-purity positive photoresist based on quaternary copolymer resin according to claim 1, characterized in that: In step (1), the number average molecular weight of the obtained quaternary copolymer resin is 12000~, and the molecular weight distribution is not higher than 1.8; the solid content of the obtained quaternary copolymer resin solution is 25~30 wt.%.
8. The method for preparing high-purity positive photoresist based on quaternary copolymer resin according to claim 1, characterized in that: In step (3), the photo-induced acid-producing agent is one of triphenylthionium salt, diphenyliodonium salt, or naphthalimide sulfonate; the amount added is 6-8% of the mass of the quaternary copolymer resin.
9. The method for preparing high-purity positive photoresist based on quaternary copolymer resin according to claim 1, characterized in that: In step (3), the alkaline additive is one of tetrabutylammonium hydroxide, tetramethylammonium hydroxide or triethylamine, and its addition amount is 5 to 15% of the mass of the photo-induced acid-producing agent.
10. The method for preparing high-purity positive photoresist based on quaternary copolymer resin according to claim 1, characterized in that: In step (3), the solvent is at least one of propylene glycol methyl ether, propylene glycol methyl ether acetate or ethyl lactate, so that the solid content of the final positive photoresist is 5~15 wt.%.
Citation Information
Patent Citations
Uhf low noise amplifier
CA585079A